2013
DOI: 10.1088/0067-0049/204/2/22
|View full text |Cite
|
Sign up to set email alerts
|

Seven-Year Multi-Color Optical Monitoring of Bl Lacertae Object S5 0716+714

Abstract: We have monitored the BL Lac object S5 0716+714 in five intermediate optical wavebands from 2004 September to 2011 April. Here we present the data that include 8661 measurements. It represents one of the largest databases obtained for an object at optical domain. A simple analysis of the data indicates that the object was active in most time, and intraday variability was frequently observed. In total, the object varied by 2.614 magnitudes in the i band. Strong bluer-when-brighter chromatism was observed on lon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 33 publications
9
25
0
Order By: Relevance
“…On JD 2456965, an extremely violent light curve was captured. The changing rate of magnitude in the B band reaches 0.347 mags·h −1 , which is close to the highest record in the R band of 0.38 mags·h −1 [9] and exceeds Dai et al's [10] 0.106 mags·h −1 and Nesci et al's [11] 0.16 mags·h −1 . Besides, the light curve on that day shows a double-peak shape overlapped by three sub-flares, and quasi-periodic oscillations (QPO) was detected.…”
Section: Light Curvessupporting
confidence: 66%
“…On JD 2456965, an extremely violent light curve was captured. The changing rate of magnitude in the B band reaches 0.347 mags·h −1 , which is close to the highest record in the R band of 0.38 mags·h −1 [9] and exceeds Dai et al's [10] 0.106 mags·h −1 and Nesci et al's [11] 0.16 mags·h −1 . Besides, the light curve on that day shows a double-peak shape overlapped by three sub-flares, and quasi-periodic oscillations (QPO) was detected.…”
Section: Light Curvessupporting
confidence: 66%
“…We note that this source is known for its persistent variability down to the timescales of hours and minutes, both in total and in polarized optical fluxes (Sasada et al 2008;Dai et al 2013;Bhatta et al 2013).…”
Section: Introductionmentioning
confidence: 88%
“…Similar findings were made by [33], where they found that their sample of BL Lacs showed complicated color-magnitude diagram behavior including hysteresis tracks, as well as achromatic flares; these indicate that different jet components dominate at different times. Dai [44] found intra-day spectral hysteresis loop patterns for the blazar S5 0716 + 714 in its color-magnitude diagram. These loop-like patterns are attributed to the differences in the amplitudes and cadences at different wavelengths [18].…”
Section: Color Indicesmentioning
confidence: 99%